EKSISTENSI BUDAYA TABE' SEBAGAI REFLEKSI NILAI KESOPANAN DALAM INTERAKSI SOSIAL PADA MASYARAKAT GOWA - Rijal, Muh.; Awaru, A. Octamaya Tenri; Arifin, Ibrahim; Hasni, Hasni; Mutiani, Mutiani (Universitas Negeri Makassar, 2025)
This The Bugis-Makassar community is known for its dynamic cultural diversity, which reflects the harmonious multiculturalism that exists in the South Sulawesi region. One of the cultures that is very famous for the Bugis-Makassar community is the Tabe' culture. The Tabe' culture represents an important aspect of the Bugis-Makassar community, which emphasizes the principles of politeness, respect, and ethical behavior in social interaction. This study aims to describe the existence of the Tabe' culture as a reflection of the value of politeness in social interaction in society. The method used in this study is a qualitative research method. Data collection was carried out by means of observation and interviews by observing the implementation of the Tabe' culture. A total of 8 teenagers, 1 community leader, became participants in this study. The results of the study show that: 1) These Tabe' values are starting to erode among modern society, especially among the younger generation, such as teenagers because they are no longer used as a guideline in interacting. 2) The existence of the Tabe' culture in the Gowa community still exists, but modern interaction patterns are more widely consumed by the community. 3) Driving factors in preserving Tabe' culture are through the role of the family in cultural education and individual awareness to always use the culture in interacting. Inhibiting factors are the influence of technology and modernization that are not faced by society and the lack of interest of the younger generation to make this tabe' culture a guideline for politeness values in society because it is considered old-fashioned.